Evaluation of Saudi population perception of the proportion of maxillary anterior teeth width ratio to the dental papilla position - Mohammad Bendahmash; Ahmed Hejazi; Feras Dhafr; Abdullah Awwad (Elsevier, 2019)
The aim of this study is to evaluate the preference of Saudi population regarding the golden proportion in the relation to the position of dental papilla. Methods: A computer image manipulation program (Adobe Photoshop CS, Adobe Systems, San Jose, CA, USA) was used to produce a golden proportion smile of the maxillary anterior teeth and to change the height of the dental papilla. A survey was then designed and sent to lay people by Google docs in different areas in Saudi Arabia. They were asked: Can you spot the difference in following pictures, which of group A is the best smile, and which from group B is the best smile, and overall which of the following is the most aesthetic smile. Results: In the evaluation of the most esthetic smile the majority of Saudi population prefer the original proportion smile and short dental papilla compared to long and with the gold standard. Large number did not notice the difference between the six different smiles 1924 participants out of which 41% (787) did notice the difference between the smile pictures.